Pengaruh Keterampilan, Lingkungan Kerja, Dan Pelatihan Terhadap Prestasi Kerja Pada LPM Econochannel FE UNJ - Asiyah Khalisa Rokhimah; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to determine the effect of skills, work environment, and training on job performance at LPM EconoChannel FE UNJ. The research method used in this research is a survey method with a quantitative approach. The population in this study were 165 members of LPM EconoChannel FE UNJ. The sampling technique used purposive sampling technique with the Slovin formula with an accuracy of 5% difficulty level so that the sample in this study amounted to 117 members. The data analysis technique used in this study uses SEM PLS (Structural Equation Modeling - Partial Least Squares) which is calculated using SmartPLS 4.0 software. Then the data analysis technique used in this study consists of measurement model analysis, structural model analysis, and direct effect hypothesis testing. The results of this study are that there is a positive and significant direct effect together between Skills, Work Environment, and Training on Work Performance at LPM EconoChannel FE UNJ.